2017
DOI: 10.1186/s12877-017-0513-5
|View full text |Cite
|
Sign up to set email alerts
|

“In the mood for ageing”: determinants of subjective well-being in older men and women of the population-based KORA-Age study

Abstract: BackgroundTo investigate risk factors associated with low subjective well-being (SWB) in men and women (≥65 years) separately with a special focus on emotional distress.MethodsA cross-sectional analysis was conducted among 3602 participants (50.6% women) aged 65-90 years (mean age 72.8 years, SD ± 5.8) from the population-based KORA-Age study conducted in 2008/2009. SWB was assessed using the WHO-5 well-being index (score range: 0 to 100). SWB was dichotomized into “low” (score ≤ 50) and “high” (score > 50) SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 46 publications
8
53
1
5
Order By: Relevance
“…Broyd et al (2016, p. 429) report that maximising SWB produces, besides economic advantages, obvious benefits for special sub-groups of the population, such as people with severe mental illness. Lukaschek et al (2017) investigated risk factors associated with low SWB in males and females aged 65 and over. Depression, anxiety, and sleeping problems seemed to be associated with low SWB in both sexes.…”
Section: Why Study Factors (Characteristics) Associated With Swb?mentioning
confidence: 99%
“…Broyd et al (2016, p. 429) report that maximising SWB produces, besides economic advantages, obvious benefits for special sub-groups of the population, such as people with severe mental illness. Lukaschek et al (2017) investigated risk factors associated with low SWB in males and females aged 65 and over. Depression, anxiety, and sleeping problems seemed to be associated with low SWB in both sexes.…”
Section: Why Study Factors (Characteristics) Associated With Swb?mentioning
confidence: 99%
“…The positive relationship between physical activity and SWB has been well documented in cross-sectional studies targeting older adults [ 11 , 12 , 13 , 14 ], some of which were carried out in HK and the UK. Based on 102 adults in HK (aged 65 years or above), Poon and Fung [ 15 ] found that physical activity was positively related to satisfaction with relationships.…”
Section: Introductionmentioning
confidence: 95%
“…However, the damage of smoking to physical functions, such as increased risks of lung cancer, atherosclerosis, and stroke [53], makes it not recommended. Previous researches have indicated that physical activity is a signi cant and robust predictor of SWB among older adults [10,17,54]. Our study shows that this prediction is still applicable for the oldest-old.…”
Section: Predictors Of Better Swbmentioning
confidence: 62%
“…They are generally unable to support themselves nancially, have poor ability to take care of themselves, are weak and sick, and have lost their spouses. Previous researches have found a downward trend in the SWB level with increasing age in the old people [17]. There may be differences in the risk factors of SWB between the young-old and the oldest-old, so it is best not to generalize.…”
Section: Introductionmentioning
confidence: 96%